Analysis of The Level of Fish Resources Utilization in The Tegal Regency Beach Waters, Central Java - Dian Sutono; Robet Perangin-angin; Suharyanto Suharyanto; Haris Hendi; Noor Zuhry (Jurnal Perikanan dan Kelautan, 2021)
This study aims to determine the relationship between the catch of each effort unit (CPUE) and the effort to catch fish resources in the coastal waters of Tegal Regency, based on the data series for the last ten years (2011-2020) with survey and interview research methods. The results showed that the existing conditions of fishing effort during the previous ten years had decreased by an average of 1.66 %. The production of fish caught and CPUE landed in Larangan Coastal Fishing Port, Tegal Regency, shows an average increasing trend of 10.91 % and 11.98 %, respectively. The calculation of the relationship between CPUE and effort provides information for MSY of 1,002.24 tons/year, TAC of 801.79 tons/year, with a utilization rate of 120.08 %. Based on the calculation data, it indicates that the average exploitation of fish resources in the coastal waters of Tegal Regency is 962.80 tons/year, which is still below the MSY (1,002.24 tons/year) but has already exceeded the TAC (801.79 tons/year) utilization rate of 120.08 %.